2022
DOI: 10.1152/jn.00639.2020
|View full text |Cite
|
Sign up to set email alerts
|

Integration of proprioceptive and visual feedback during online control of reaching

Abstract: Visual and proprioceptive feedback both contribute to perceptual decisions, but it remains unknown how these feedback signals are integrated together or consider factors such as delays and variance during online control. We investigated this question by having participants reach to a target with randomly applied mechanical and/or visual disturbances. We observed that the presence of visual feedback during a mechanical disturbance did not increase the size of the muscle response significantly but did decrease v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…bodyversus world-centred; [52]), accuracy [53] and processing delay [49,54]. Thus, motor microregulations would now depend on a more complex mixture of predictive and feedback mechanisms, the latter operating on weighted estimation of vision and proprioception [52,53,55,56], which will eventually influence the dynamics of sensorimotor control loops. It is worth noting that the partial alternation of submovements observed in the solo task with eyes open (in-phase coordination only) also highlights a possible asymmetry between the right (dominant) and left (non-dominant) hands.…”
Section: Discussionmentioning
confidence: 99%
“…bodyversus world-centred; [52]), accuracy [53] and processing delay [49,54]. Thus, motor microregulations would now depend on a more complex mixture of predictive and feedback mechanisms, the latter operating on weighted estimation of vision and proprioception [52,53,55,56], which will eventually influence the dynamics of sensorimotor control loops. It is worth noting that the partial alternation of submovements observed in the solo task with eyes open (in-phase coordination only) also highlights a possible asymmetry between the right (dominant) and left (non-dominant) hands.…”
Section: Discussionmentioning
confidence: 99%
“…Since sensory predictions provide an estimate of where the limb is expected to be at the current time, they can help overcome delays that would otherwise lead to out-of-date position estimates based on sensory feedback alone (Shadmehr et al, 2010). A previous study offered a more complex dynamic Bayesian model with Kalman filtering that attempted to account for sensory delays in an active arm movement task (Crevecoeur et al, 2016; Kasuga et al, 2022). Notably, these authors also concluded that individuals are likely to base state estimates on unimodal (in their case, reliant on proprioceptive feedback) in the face of sensory delays.…”
Section: Discussionmentioning
confidence: 99%
“…Either way, a feedback-based estimate of the moving limb that relies on multisensory integration is likely to be unreliable relative to an estimate made with the same sensory input when the limb is stationary. During active limb movements, this problem may be partially resolved by the availability of sensory prediction signals, which provide a real-time prediction of the current limb position and thus can be used to resolve erroneous motor commands (Crevecoeur et al, 2016; Kasuga et al, 2022). However, the availability of sensory prediction signals does not fully resolve the problem because real albeit delayed sensory feedback is still required to respond to unexpected environmental perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Kasuga et al (2022) suggest a two-stage process for integration of sensory information. In an initial subcortical stage, information from each sensory modality is processed separately, allowing fast error-correction based on only proprioceptive feedback, whereas in the second cortical stage, different sensory modalities are integrated (Kasuga et al, 2022). In the second stage, when information from various modalities is integrated into a unified experience, visual information dominates.…”
Section: Metacognitive Judgmentsmentioning
confidence: 98%